Associations Between 25-Hydroxyvitamin D, Kidney Function, and Insulin Resistance Among Adults in the United States of America - Geng, Jiwen; Qiu, Yuxuan; Li, Yupei; Li, Jiameng; Liao, Ruoxi; Du, Heyue; Jiang, Luojia; Wang, Liya; Qin, Zheng; Yang, Qinbo; Yu, Qiao; Zhang, Zhuyun; et al. (Frontiers in Nutrition, 2022)
Background: Although many molecular studies have tried to explore the relationship between vitamin D metabolism and kidney function, the association between 25-hydroxyvitamin D and kidney function is still controversial. Previous studies reported that low vitamin D status and decreased kidney function were associated with insulin resistance (IR). However, neither of them was confirmed by large population-based studies. This study evaluated the associations between 25-hydroxyvitamin D and kidney function and the associations between both of them and insulin resistance among adults in the United States. Method: We analyzed 36523 adults from the National Health and Nutrition Examination Survey (2001–2014). Kidney function was assessed by the estimated glomerular filtration rate (eGFR), and IR was assessed by homeostasis model assessment (HOMA-IR). All data were survey-weighted, and corresponding linear regression models were performed to examine the associations. Results: The mean serum 25-hydroxyvitamin D levels were increased in participants with decreased kidney function (eGFR <90 ml/min/1.73 m2, and each unit of decreased serum 25-hydroxyvitamin D concentrations predicted 0.453 mL/min/1.73 m2 (95% CI: 0.426 to 0.480, P<0.0001) higher eGFR. In addition, each unit of decreased eGFR was associated with 0.007 higher HOMA-IR, while each unit of decreased serum 25-hydroxyvitamin D concentrations led to 0.025 higher HOMA-IR. Conclusions: Serum 25-hydroxyvitamin D concentrations were negatively associated with kidney function. IR appears in the early stage of kidney dysfunction, and both serum 25-hydroxyvitamin D concentrations and kidney function are negatively associated with IR. Clinicians should maintain appropriate serum 25-hydroxyvitamin D concentrations and doses of vitamin D supplements for different populations. The underlying mechanism of these associations still needs more research, especially the negative association between serum 25-hydroxyvitamin D concentrations and kidney function.